2D Monoelemental Arsenene, Antimonene, and Bismuthene: Beyond Black Phosphorus. Issue 21 (10th February 2017) - Pumera, Martin; Sofer, Zdeněk
Abstract : Two‐dimensional materials are responsible for changing research in materials science. After graphene and its counterparts, graphane, fluorographene, and others were introduced, waves of renewed interest in 2D binary compounds occurred, such as in metal oxides, transition‐metal dichalcogenides (most often represented by MoS2 ), metal oxy/hydroxide borides, and MXenes, to name the most prominent. Recently, interest has turned to two‐dimensional monoelemental structures, such as monolayer black phosphorus and, very recently, to monolayer arsenic, antimony, and bismuth. Here, a short overview is provided of the area of exponentially increasing research in arsenene, antimonene, and bismuthene, which belong to the fifth main group of elements, the so‐called pnictogens. A short review of historical work is provided, the properties of bulk allotropes of As, Sb, and Bi discussed, and then theoretical and experimental research on mono‐ and few‐layered arsenene, antimonene, and bismuthene addressed, discussing their structures and properties. Abstract : 2D As, Bs, and Bi – arsenene, antimonene, and bismuthene – are monoelemental nanomaterials. Their properties depend significantly on crystal structure, on the number of layers or on the doping. They are easily obtained from their bulk counterparts or as deposited on surfaces. An overview of their properties is provided and their applications predicted.